Enhancing the Jurisdiction of the Regional Notary Supervisory Council of West Nusa Tenggara Province in the Advancement and Oversight of Notaries - Putra, Guntur Ilman; Hasanah, Siti; Jiwantara, Firzhal Arzhi; Septyanun, Nurjannah (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The position and authority of a Notary is crucial in ensuring legal clarity for individuals while undertaking legal activities. The behavior and actions of a Notary are very susceptible to abuse of their professional position, which can have negative consequences for society. In order to mitigate community losses, the establishment of a regulatory entity to oversee notaries is important. The research use the normative law research method to identify a legal rule, legal principles, and legal doctrines that can address the current legal difficulties. According to the findings of the research on the Enhancement of Authority of the Notary Regional Supervisory Council in the Development and Oversight of Notaries, the Notary Supervisory Board is empowered to conduct administrative oversight, and sanctions serve as legal repercussions for the decisions made by the Supervisory Board against a Notary who breaches the regulations pertaining to the execution of their duties in the position of a Notary, as stipulated in Legislation regarding the role and responsibilities of a Notary.